Entrepreneurial finance and institutional logics in an emerging economy - Worakantak, Jirawat; Newbery, Robert; Kimmitt, Jonathan (International small business journal, 2024)
Entrepreneurs raise money from multiple funding sources over time; however, studies of entrepreneurial finance typically focus on a dyadic view based on Global North institutional scaffolds. Taking a contextualised approach that understands funding as situated in local conditions, this research explores the influence of an emerging economy context on a financing process that incorporates multiple sources. Based on analysis of 36 interviews with entrepreneurs and financiers in Thailand, the research offers a model that identifies emerging entrepreneur–financier relationships and strategies for navigating multiple logics. Accessing funding involves a process of deal-making that requires multiple foci of attention over time. This article advances institutional theory by reclassifying how entrepreneurs interact with heterogeneous resource holders. Divergent logical pathways of relational formation are found among various types of financiers, suggesting an underlying institutional logic is not universal. Instead, it depends on the habitual organising principles of the focal actors and strategies adopted to manage the requirements of multiple funders.